Comparative Evaluation of Ketamine–Propofol versus Ketamine–Diazepam for Total Intravenous Anesthesia in ERAS-Guided Day Case Surgery (The Insight, 2025)
Introduction: ERAS protocols in day-case surgeries reduce stress and promote faster recovery. TIVA is favored for its controllable depth and quick emergence. This study compares ketamine–propofol and ketamine–diazepam anesthesia regarding perioperative stability and recovery outcomes in ERAS-guided day-case surgeries. Methods & Materials: This one-year prospective comparative study (July 2024–June 2025) at Gazi Medical College, Khulna, included 60 adults undergoing ERAS-guided day-case surgery. Patients were randomized into two groups: Group A (Ketamine + Propofol) and Group B (Ketamine + Diazepam). Perioperative parameters, recovery, PONV, pain, complications, and hospital stay were analyzed using SPSS v26.0, with p < 0.05 considered significant. Results: Both groups were comparable in demographics, ASA status, types of surgery, and intraoperative parameters. Group A (ketamine–propofol) demonstrated significantly better hemodynamic stability, smoother recovery from anesthesia, and a lower incidence of PONV (p < 0.05). Recovery was faster in Group A, with earlier oral intake and ambulation, shorter PACU stay, and reduced hospital stay (all p
Keywords: Total Intravenous Anesthesia (TIVA); Enhanced Recovery after Surgery (ERAS); Day Case Surgery